Less human and help-worthy: Sexualization affects children's perceptions of and intentions toward bullied peers. (November 2019) - Pacilli, Maria Giuseppina; Spaccatini, Federica; Barresi, Concetta; Tomasetto, Carlo
In Western cultures, the sexualization of children has increased over the past decades. In two studies, we investigated the consequences of children's sexualization for their peers' willingness to provide help in a case of bullying. In both studies, children (total N = 396; ages 7 to 11 years) were randomly assigned to view either a sexualized or non-sexualized target and answered questions about the target's traits and treatment. Our findings provide evidence that early sexualization exposes preadolescent children to the dehumanizing consequences associated with adult women's sexualization. We found that sexualized targets were perceived as less than fully human in terms of both human nature and human uniqueness (Studies 1 and 2) and that, among girls, human nature ratings mediated the association between sexualization and reduced helping intentions toward both male (Study 2) and female targets (Studies 1 and 2).